2020
DOI: 10.37394/23207.2020.17.12
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Financial Effects between Islamic and Conventional Banking

Abstract: This study discusses a comprehensive analysis of the effect of competition and financial effects between Islamic and conventional banks. This study conducts in Asian countries i.e., Indonesia, Malaysia, Singapore, Thailand, Philippines, Brunei. The first step, introducing a descriptive study mapping that analyzes the characteristics the main among the sharia and conventional banking sectors. Then in the second step, the competitiveness level of Islamic and conventional banks is measured using the Lerner index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The research concluded that marketing methods based on the floating markets by targeting floating market share could increase the competitiveness of Islamic banks. The following study was conducted by mentioning that the target market of rational and non-Muslims while maintaining attention to Muslims as the main spiritual basis, can increase the competitiveness of Islamic banks (Mawardi et al 2020;Cupian and Abduh 2017).…”
Section: T-test Results (Hypothesis Test)mentioning
confidence: 99%
See 1 more Smart Citation
“…The research concluded that marketing methods based on the floating markets by targeting floating market share could increase the competitiveness of Islamic banks. The following study was conducted by mentioning that the target market of rational and non-Muslims while maintaining attention to Muslims as the main spiritual basis, can increase the competitiveness of Islamic banks (Mawardi et al 2020;Cupian and Abduh 2017).…”
Section: T-test Results (Hypothesis Test)mentioning
confidence: 99%
“…The average competitiveness of banks is lower than the level of competition in the banking market. His research specifically seeks to determine whether the competitiveness of Islamic banks is significantly higher or lower than that of conventional banks (Louati, Louhichi, and Boujelbene 2016;Sukardi and Wijaya 2013;Ishak 2019;Ben Bouheni and Ammi 2015;Mawardi et al 2020).…”
Section: Competitivenessmentioning
confidence: 99%
“…The work [9] reveals interesting theoretical models that describe the work of the bank as an institution of delegated monitoring. One of them is based on the following preconditions.…”
Section: Resultsmentioning
confidence: 99%
“…Effective management of banking concerns the operational efficiency of the bank can be considered in many aspects [9].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Islamic banks are a type of banking known for applying Sharia principles and not charging usury (Billah et al, 2024). It has become the basis for most Muslims in Indonesia to do all things, especially in making transactions based on Islamic principles (Bakry et al, 2021;Mawardi et al, 2020). However, the Islamic banking market is still tiny despite the majority of Indonesia's population being Muslim.…”
Section: Introductionmentioning
confidence: 99%